2016
DOI: 10.1093/infdis/jiw168
|View full text |Cite
|
Sign up to set email alerts
|

MICAMutant A5.1 Influences BK Polyomavirus Reactivation and Associated Nephropathy After Kidney Transplantation

Abstract: These findings identify the MHC-related MICA as an immunogenetic factor that may functionally influence anti-BKPyV immune responses and infection outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Two decades after the report of Pappo et al and despite general outcome improvements, the care of patients with PyVAN remains a daunting task, mostly due to the complexity of immunological responses and poorly understood factors influencing the susceptibility to the infection .…”
Section: Discussionmentioning
confidence: 99%
“…Two decades after the report of Pappo et al and despite general outcome improvements, the care of patients with PyVAN remains a daunting task, mostly due to the complexity of immunological responses and poorly understood factors influencing the susceptibility to the infection .…”
Section: Discussionmentioning
confidence: 99%
“…About BK virus, Tonnerre et al . found a lower incidence of BK virus reactivation in recipient transplanted with renal graft carrying MICA A5.1 mutant (a ligand for the activating NK receptor NKG2D) . These data suggest that intragraft MICA expression may a significant incidence on BK virus reactivation after transplantation and may indicate a protective role for MICA A5.1.…”
Section: Discussionmentioning
confidence: 76%
“…In a group of 90 CMV-negative patients having received a first renal transplantation from a CMV-positive donor, there was no significant difference between the KIR A and B haplotypes or the number of activating or inhibitory KIRs in terms of the occurrence of CMV disease [13]. About BK virus, Tonnerre et al found a lower incidence of BK virus reactivation in recipient transplanted with renal graft carrying MICA A5.1 mutant (a ligand for the activating NK receptor NKG2D) [14]. These data suggest that intragraft MICA expression may a significant incidence on BK virus reactivation after transplantation and may indicate a protective role for MICA A5.1.…”
Section: Discussionmentioning
confidence: 98%
“…Stress conditions following transplantation cause a general inflammatory status in recipients, which could increase MICA production. In kidney allografts, an enhanced MICA expression has been reported on epithelial and endothelial cells in response to ischemia-reperfusion injury, acute rejection, or viral infection ( 27 , 37 ). Thus, the presence of MICA in the donor organ could elicit NK and T cell activating responses via the NKG2D receptor.…”
Section: Discussionmentioning
confidence: 99%
“…A CMV transmission to allograft recipients may occur via donor organs as the virus is able to infect several types of human kidney cells and thus can reside in the graft ( 36 ). In contrast to other tissues, a notably strong MICA protein expression has been described in kidney allografts ( 37 , 38 ). Consequently, MICA/NKG2D axis polymorphisms of the donor organ or the recipient may affect immune antiviral NK and T cell responses against CMV.…”
Section: Introductionmentioning
confidence: 99%